ANALISIS KENDALA DALAM PEMBELAJARAN IPA DI KELAS RENDAH III SD NEGERI 24 PANGKALPINANG - Miranti Amanda Sari; Hilyatul Ashfiyaa; Lysia Rizki Harinda; M Iqbal Arrosyad (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Natural Science (IPA) learning in lower grades of Elementary School (SD) requires special strategies to foster students' understanding of concepts and science process skills. This study aims to describe the obstacles in science learning in the lower grade III of SD Negeri 24 Pangkalpinang. The research used a qualitative research method with the subjects being lower grade teachers of SD Negeri 24 Pangkalpinang. The study was conducted on October 9, 2025. Data collection techniques involved in-depth interviews with teachers and documentation related to learning facilities. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study showed that teachers implemented mixed methods such as demonstrations, simple experiments, discussions, and stories to create contextual learning, but several indicators of major obstacles were found, such as limited time to carry out simple experiments, lack of availability of teaching aids, and the absence of a special laboratory.